2009
DOI: 10.3181/0903-rm-116
|View full text |Cite
|
Sign up to set email alerts
|

Enterovirus 71 Infection of Human Dendritic Cells

Abstract: Enterovirus 71 (EV71) causes death and long-term neurologic sequelae in hundreds of thousands of young children, but its pathogenesis remains elusive. Dendritic cells (DCs) play a crucial role in antiviral immunity by functioning as professional antigen-presenting cells to prime T cells and by secreting cytokines to modulate immune responses. Here, we show that EV71 productively infected human immature DCs and expressed viral antigen in DCs. EV71 entry into DCs was partially mediated by DC-SIGN. Further analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
65
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 34 publications
5
65
3
Order By: Relevance
“…Survival rates and clinical scores indicated that the treated animals died significantly faster than the untreated infected mice (Fig. 8), thus supporting previous observations with IL-6 KO mice (26). Consistently, mice cotreated with anti-IL-6 antibodies at the time of infection displayed severe tissue (limb muscle) damage, with myonecrosis even more pronounced than in the untreated infected animals, and spleen atrophy (Fig.…”
Section: Vol 85 2011 Role Of Il-6 During Ev71 Infection 3071supporting
confidence: 77%
See 2 more Smart Citations
“…Survival rates and clinical scores indicated that the treated animals died significantly faster than the untreated infected mice (Fig. 8), thus supporting previous observations with IL-6 KO mice (26). Consistently, mice cotreated with anti-IL-6 antibodies at the time of infection displayed severe tissue (limb muscle) damage, with myonecrosis even more pronounced than in the untreated infected animals, and spleen atrophy (Fig.…”
Section: Vol 85 2011 Role Of Il-6 During Ev71 Infection 3071supporting
confidence: 77%
“…Previous literature reported that IL-6 knockout (KO) mice were more susceptible to EV71 infection than their parental counterparts, suggesting a protective role for IL-6 during EV71 infection (26). In contrast, we found that anti-IL-6 antibody treatment resulted in better survival and clinical outcome, thus suggesting instead that IL-6 is detrimental to the host.…”
Section: Vol 85 2011 Role Of Il-6 During Ev71 Infection 3071contrasting
confidence: 55%
See 1 more Smart Citation
“…The cellular and humoral immune responses, such as represented by T cells and the interleukin-6 (IL-6) driven response, are both essential for decreasing the viral load and mortality in EV71-infected mice. 12,13 In humans, an extensive peripheral and central nervous system inflammatory response, with abnormal IL-10, IL-13 and interferon-c (IFN-c) cytokine production as well as lymphocyte depletion, appears to be responsible for the pathogenesis of EV71-associated pulmonary oedema. [14][15][16] However, to date the mechanism of the cellular immune response to EV71 has not been elucidated in detail.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…Blood samples were obtained on days 1-7 after onset, discharge from the hospital (day [7][8][9][10][11][12][13][14] and the fully recovered stage (defined as 1 month after illness onset), respectively. All samples were collected specifically for this study and were coded to protect confidentiality.…”
Section: Recruitment and Sample Collectionmentioning
confidence: 99%